Menjadi Kampung Tematik dan Wisata Religi di Desa Sumur, Kendal - Thomasonan Lutfie Prananto; Lutfie P, Thomasonan (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2025)
Poverty and environmental problems in settlements in Kendal Regency are challenges in sustainable development. This community service program aims to improve community welfare through the concept of thematic villages and religious tourism in Sumur Village, Brangsong District. The methods used include counseling to the community regarding environmental management and economic development based on local potential. The results of the activity showed that the community began to understand the concept of thematic villages and the importance of religious tourism as a source of village income. This program also increases public awareness in utilizing yards as an additional economic resource. It is hoped that the implementation of thematic villages can continue with the support of local governments and universities